Structural Change and Productivity Growth in Guinea - Mijiyawa, Abdoul' Ganiou (World Bank, Washington, DC, 2020)
This paper documents that structural change positively contributed to labor productivity growth in Guinea during 2006-15. However, the contribution of structural change to productivity growth was modest (about one percentage point per year on average), because labor moved from agriculture, the least productive sector, into other relatively low-productivity activities, such as wholesale and retail trade and community services. Although such services are more productive than agriculture, they are low-productivity activities because of the high level of informality. The paper also finds that the contribution of structural change to productivity growth has declined over time, mainly due to the increased labor market rigidity, lower competitive real exchange rate, declining human capital, and weaker government effectiveness. The paper provides a discussion of the policy implications of the findings.